Principles of State Administrative Court In Indonesia - Sofi Yuliniar (JUSTICES: Journal of Law, 2023)
In a principle of state administrative justice in Indonesia, there are two differences where this justice system lives in a rule of law state, the first is unity of jurisdiction, which means a unit of jurisdiction which will certainly be embraced by a rule of law country, where only one unit recognizes the entire set of courts, namely there is in ordinary courts such as (general courts) and quite unfamiliar with PTUN. Furthermore, the second in the duality of jurisdiction adopted by countries where laws are adhered to is the general court and Administrative Court. Now, where the general court is at the supreme court, while PTUN blends in with the state. Now, in these two cases, it is not only the organizational structure of the court that differs, but the legal subjects or procedural law are actually different. Now, in Indonesia, this is quite unique because there is a research result that we know very well, which is closer to a unified system of jurisdiction, but when viewed from the principles of justice or procedures for resolving disputes, it is closer to the system of dual jurisdiction, so that in writing want to conclude that the justice system in Indonesia follows a mixed system.